2017
DOI: 10.1007/s00038-017-1012-3
|View full text |Cite
|
Sign up to set email alerts
|

Burden of cardiovascular diseases in the Eastern Mediterranean Region, 1990–2015: findings from the Global Burden of Disease 2015 study

Abstract: ObjectivesTo report the burden of cardiovascular diseases (CVD) in the Eastern Mediterranean Region (EMR) during 1990–2015.MethodsWe used the 2015 Global Burden of Disease study for estimates of mortality and disability-adjusted life years (DALYs) of different CVD in 22 countries of EMR.ResultsA total of 1.4 million CVD deaths (95% UI: 1.3–1.5) occurred in 2015 in the EMR, with the highest number of deaths in Pakistan (465,116) and the lowest number of deaths in Qatar (723). The age-standardized DALY rate per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…The eastern Mediterranean region, comprising 22 countries, witnessed 1.3 million CVD deaths in 2015; 16% of these were in Egypt. 13 This calls for tailored programmes to reduce the burden of risk factors in the country. A Cochrane Systematic Review showed that risk-factor interventions may lower blood pressure, BMI and waist circumference in low-and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…The eastern Mediterranean region, comprising 22 countries, witnessed 1.3 million CVD deaths in 2015; 16% of these were in Egypt. 13 This calls for tailored programmes to reduce the burden of risk factors in the country. A Cochrane Systematic Review showed that risk-factor interventions may lower blood pressure, BMI and waist circumference in low-and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite health policies implemented in the last decades and increasingly available therapeutic options, hypertension and cardiovascular disease (CVD) continue to be the main cause of disability, morbidity and mortality, both in Europe and in the United States [1,2]. Primary and secondary prevention continues to address individuals who have experienced disease or present with one or more risk factors; furthermore, primordial prevention has been suggested for the attainment of global health at the population level [3,4]. In fact, the World Health Organization (WHO) recently highlighted the importance of controlling blood pressure as millions of individuals have CVD worldwide, accounting for 31% of the world’s population, of which 80% experience either heart diseases and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have remarked on the importance of a healthy diet, emphasizing its impact on the health and prevention of CVD 15,34,49 . Some of the unhealthy habits that cause CVD include the high consumption of sodium, trans fats, cholesterol, and salt, along with the low consumption of fiber, fruit, vegetables, nuts, seeds 3,12,15,17,49 , and omega 3@@@ 49 . In contrast, the presence of flavonoids in the diet presents an inversely proportional association with cardiovascular disease mortality 50 .…”
Section: Discussionmentioning
confidence: 99%